sv-COVID-19 - Språkbanken Text (University of Gothenburg, 2024)
sv-covid-19 is a collection of Swedish news texts, scientific and
popular science articles and articles from certain blogs and social
media wuch as Flashback and Twitter, which started to be published at
the beginning of the coronavirus pandemic (early 2020). The latest
verision of the corpus consists of approximately eight million words
and 9000 articles. The corpus contains various text types and texts
with different stylistic levels. The texts have been marked up with
word class tags, morphological analysis and lemma, as well as some
structural and functional information, such as author names.

sv-covid-19 är en samling svenska nyhetestexter, vetenskapliga och
populärvetenskapliga artiklar och artiklar från vissa bloggar och
sociala medier, till exempel Flashback och Twitter, som började
publiceras i början av coronaviruspandemin (tidigt 2020). Korpusen
består av drygt åtta miljoner ord och 9000 artiklar. Korpusen
innehåller olika texttyper och texter med olika stilnivåer. Texterna
har märkts upp med ordklasstaggar, morfologisk analys och lemma, samt
viss strukturell och funktionell information, som till exempel
författarnamn.
sv-COVID-19
Keywords: Language Technology (Computational Linguistics); news texts; social media; scientific articles; medical articles; corpus; Natural Language Processing; Språkbehandling och datorlingvistik